2019
DOI: 10.1002/cbm.2108
|View full text |Cite
|
Sign up to set email alerts
|

Parallel‐process trajectories of exposure to violence and psychological distress among justice‐involved youth

Abstract: Background Researchers have raised awareness of high levels of violence exposure among justice‐involved adolescents and its association with psychological distress, yet the relationship between the violence and psychological distress has rarely been studied longitudinally. Aim This study aimed to gain understanding of the relationship between long‐term exposure to violence and the development of psychological distress among justice‐involved adolescents. Methods We examined exposure to violence and emergent psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Overall, of the reported prevalence rates, witnessing community violence was the most prominent form of exposure across developmental stages. Study findings generally demonstrated trends of higher rates of witnessing and victimization as the average participant age increased, except for one study that suggested exposure rates decreased over time for Latinx youth (Reid & Loughran, 2019). Reported exposure types included witnessing violence with a deadly weapon, physical assaults or fights, robberies or muggings, and gang fights; a less common but still notable reported exposure was witnessing someone being killed with a weapon.…”
Section: Resultsmentioning
confidence: 87%
“…Overall, of the reported prevalence rates, witnessing community violence was the most prominent form of exposure across developmental stages. Study findings generally demonstrated trends of higher rates of witnessing and victimization as the average participant age increased, except for one study that suggested exposure rates decreased over time for Latinx youth (Reid & Loughran, 2019). Reported exposure types included witnessing violence with a deadly weapon, physical assaults or fights, robberies or muggings, and gang fights; a less common but still notable reported exposure was witnessing someone being killed with a weapon.…”
Section: Resultsmentioning
confidence: 87%
“…These study findings support the propositions of General Strain Theory predicting that strain impacts negative emotions, which in turn, decreases youth’s ability to control antisocial behavior (Agnew & Brezina, 2019). Experiencing multiple, chronic, or prolonged adversity, compounded by COVID-19, is likely to cause youth difficulty in modulating their emotions resulting in increased antisocial behavior (Reid & Loughran, 2019, 2021; Van der Kolk, 2005). Disproportionately high levels of strain in the form of ACEs experienced by justice-involved youth (Baglivio et al, 2014)—now exacerbated by COVID-19 conditions—necessitates a trauma-informed approach designed to address the intersection between COVID-19, ACEs, and health disparities (Sonu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Children and youth exposed to violence also have an increased risk of developing aggressive attitudes, engaging in drug and alcohol abuse, or committing suicide and violence (Reid 2018). The long-term, detrimental effects of ETV during childhood and adolescence have been substantiated by large bodies of research from various fields (e.g., Perepletchikova and Kaufman 2010;Piquero et al 2006;Putnam 2006;Reid and Loughran 2019a). Specific to this study, Farrell and Zimmerman (2017) found that contemporaneous and acute ETV was significantly related to long-term future violent offending.…”
Section: Exposure To Violencementioning
confidence: 71%